Increased systemic immune activation and inflammatory profile of long-term HIV-infected ART-controlled patients is related to personal factors, but not to markers of HIV infection severity. (1st March 2015) - Bastard, Jean-Philippe; Fellahi, Soraya; Couffignal, Camille; Raffi, François; Gras, Guillaume; Hardel, Lucile; Sobel, Alain; Leport, Catherine; Fardet, Laurence; Capeau, Jacqueline; Leport, C.; et al.
Abstract: Objectives: The objective of this study was to analyse the respective roles of personal factors and HIV infection markers on the systemic immune activation/inflammatory profile of long-term antiretroviral treatment-controlled patients. Patients and methods: A panel of soluble immune activation/inflammatory biomarkers was measured in 352 HIV-infected treatment-controlled patients from the APROCO-COPILOTE cohort, all of whom were started on a PI in 1997–99 and had a final evaluation 11 years later, and in 59 healthy controls. Results: A total of 81.5% of the patients were male, with the following characteristics: median age 49 years; 620 CD4 cells/mm 3 ; 756 CD8 cells/mm 3 ; CD4/CD8 ratio 0.81; BMI 23.0 kg/m 2 ; waist-to-hip ratio 0.95. Markers of inflammation—high-sensitivity (hs) IL-6 (median and IQR) (1.3 pg/L, 0.7–2.6), hs C-reactive protein (CRP) (2.1 mg/L, 0.9–4.5) and D-dimer (252 ng/mL, 177–374)—were elevated compared with healthy controls ( P  < 0.001) and strongly related to each other, as were markers of immune activation [soluble (s) CD14 (1356 ng/mL, 1027–1818), β2 -microglobulin (2.4 mg/L, 2.0–3.1) and cystatin-C (0.93 mg/L, 0.82–1.1)]. Inflammatory and immune activation markers were also associated with each other. In HIV-infected patients: age was related to D-dimer, β2 -microglobulin and cystatin-C levels; being a smoker was related to increased IL-6 and cystatin-C; and BMI and waist-to-hip ratio were related to CRP. Conversely, markers of HIV infection, current CD4 or CD8 values, CD4 nadir, CD4/CD8 ratio, AIDS stage at initiation of PIs, current viral load and duration of ART were not associated with immune activation/inflammation markers. Conclusions: In these long-term treatment-controlled HIV-infected patients, all systemic markers of inflammation and immune activation were increased compared with healthy controls. This was related to demographic and behavioural factors, but not to markers of severity of the HIV infection. Intervention to decrease low-grade inflammation must thus prioritize modifiable personal factors.